Endoscopic thoracic sympathectomy--its effect in the treatment of refractory angina pectoris - Stritesky, Martin; Dobias, Milos; Demes, Rudolf; Semrad, Michal; Poliachova, Eva; Cermak, Tomas; Charvat, Jiri; Malek, Ivan (Interactive cardiovascular and thoracic surgery, 2006)
OBJECTIVE: To document an improvement in the quality of life in a group of patients with refractory angina and videothoracoscopic sympathectomy (VTSY) during the early postoperative period and a six-month follow-up. METHODS: Ten patients with angina CCS IV refractory to a conventional therapy underwent VTSY between the years 1998 and 2002 at our institution. All patients underwent a complex preoperative evaluation, including pain assessment using a visual analog scale (VAS). Proximal thoracic sympathetic blockage was performed in all patients as a diagnostic test. The resection of bilateral Th2-Th4 ganglions was performed under general anesthesia and selective lung ventilation. All patients were monitored 6 months after the VTSY. RESULTS: No deaths occurred in our group of patients, with an average hospital stay of 4.1 days. Nine of the ten operated patients referred an important subjective relief of pain. There was a drop from 10 to 4 according to VAS (P<0.05), and from 4 to 2.4 according to CCS (P<0.05). Decreases in basal heart rate, norepinephrine level, and an occurrence of ventricular premature beats reached the level of statistical significance. CONCLUSIONS: The increasing number of patients with refractory angina prompted a search for an effective and safe therapy to improve the quality of their life. New evidence in the pathophysiology of an ischemic myocardium and investigation of the impact of thoracic sympathectomy suggests sympathetic denervation seems to be a possible alternative method for the treatment of refractory angina pectoris.